Eucalyptus short-rotation coppice for solid fuel production - Eufrade Junior, Humberto de Jesus [UNESP]; Nakashima, Gabriela Tami; Yamaji, Fábio Minoru; Guerra, Saulo Philipe Sebastião [UNESP]; Ballarin, Adriano Wagner [UNESP] (Elsevier, 2017)
Briquetting provides a homogenous product that has high density, and reduced transport and storage costs in the wood chips supply chain. Few studies evaluated briquettes from eucalypt short-rotation coppice (SRC) managed under tropical conditions and also its energy potential was not clearly defined. The aim of this paper was to assess the quality of briquettes produced from Eucalyptus SRC. The SRC biomass was separated into stem, branches, leaves and mix (produced according to the actual availability in the forest). The physical, chemical and mechanical properties were analyzed. A SEM-EDS (scanning electron microscopy equipped with an energy-dispersive spectroscopy detector) analysis of ashes from SRC biomass was carried out. Results showed higher energy properties in leaves than for woody fractions, however, its use was limited due to higher content of ash (3.1%) and a poor mechanical performance. Stem and mix were more suitable for energy purposes, and both treatments reached an energy potential of 14.2 GJ m−3. SEM-EDS analysis showed that the elements Ca, K and Mg represented approximately 80% of the mineral component. It was found that the presence of other regular structures predominantly comprising the elements Fe and Al may lead to a serious technical problem. However, briquetting appears as a feasible option to increase added value of forest products from young energetic plantations.
Keywords: Briquettes; Heating value; Mechanical properties; SRC biomass